Campos de atuação e os desafios da arqueologia empresarial no Brasil - Jacques, Clarisse Callegari; de Carvalho, Adriano Batista (Brasiliana: Journal for Brazilian Studies, 2021)
In the context of an increase in infrastructure projects at the same time as Brazilian legislation seeks to regulate and guide permissions for archaeologists to undertake research associated with environmental licenses, the number of archaeology consulting firms has been growing in numbers. Other fieldworks worth mentioning concerning contract archaeology are cave evaluations, restoration of the historic building as well as museum consulting. Many issues have emerged along with the growth of research in contract archaeology. One of the most discussed is the research quality and archaeologist’s ethic commitment. Dialogue between archaeologists who work in different research contexts is crucial to the evolution of this debate, especially when social sciences lack governmental funding and seek society acknowledgement.